Proceedings of MEST 2012 : Exponential Type Orbitals for Molecular Electronic Structure Theory - Hoggan, Philip E. (Advances in quantum chemistry, 2013)
Advances in Quantum Chemistry presents surveys of current topics in this rapidly developing field that has emerged at the cross section of the historically established areas of mathematics, physics, chemistry, and biology. It features detailed reviews written by leading international researchers. This volume focuses on the theory of heavy ion physics in medicine. Advances in Quantum Chemistry presents surveys of current topics in this rapidly developing field and this volume focuses on the theory of heavy ion physics in medicine.